Autorenvarianten in Prospers De vocatione omnium gentium? Einige methodische Überlegungen - Weber, Dorothea (Augustinianum, 2010)
The Author replies to a review recently published by Franco Gori in the journal Augustinianum. The point of disagreement advanced by the Author is the basic hypothesis which she finds in Gori’s essay, according to which textual variants in De vocatione omnium gentium go back to the author himself, i.e., to Prosper of Aquitaine.